(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
The traditional use of Ayurvedic formulations is a widely accepted therapeutic option especially in chronic diseases. The quality of Bhasma depends on the manufacturing procedures and dosage schedule mentioned as per the classical texts. The Ayurvedic formulations are being considered as therapeutic potential agent as they have been evaluated based on experimental analysis. However for global acceptance the safety is a concern, the WHO has recognized Ayurveda as a part of integrated system of medicine. In view of developments an investigation is undertaken to evaluate the safety of a Bhasma. Rasa Bhasma, an organo-metallic compound is one such compound described in Rasashastra for treating acute and chronic diseases. It is prepared in several steps, which increases its therapeutic potential and eliminates its metallic toxicity. Among the various Bhasma preparations a popularly recommended and used formulation of Rasa Bhasma was selected for the toxicology study. In the present investigation it is proposed to undertake a short (acute) term pre clinical acute toxicity test on Rats, to obtain the safety profile. The proposed experiment has been under taken after taking the approval of Institutional Approval Ethical Committee, SIPRA Labs to conduct the experiment at their centre. Acute toxicity study on 15 Wistar Rats, have been randomizingly selected and divided into two groups to receive the test compound in a vehicle and identified as a TD and a vehicle group to receive Honey, Water for a period of 7 days and identified as VC. 8 (3VC+5TD) animals after 48 hours and remaining 7 (2VC+5TD) animals after 7 days were subjected for clinical haematology, chemistry and necropsy observation. After 7 days of exposure to the test compound of recommended therapeutic dose, no significant changes in haematological parameters & clinical chemistry parameters were found. No Pre-terminal deaths occurred in rats, which received test compound at therapeutic dose levels. No abnormalities in physical, physiological, clinical chemistry, hematological parameters and no gross necropsy changes were observed on administration (oral) of test compound prepared according to the classical literature. At this level of study, it may be concluded that Rasa Bhasma is safe as per toxicological study and can be subjected for further study of clinical evaluation.